On the Origin of the Crusade Army from the Perspective of Agenda-setting Theory：A Case Study of UrbanⅡ’s Sermon - ZHANG, Shiyao (Journal of Research for Christianity in China (JRCC), 2024)
The Crusade was one of the important historical events in the Middle Ages of Western Europe. The war in the name of religion since 1096 had a profound impact on Western Europe and the Near East. It is well known that an important reason for the Crusade was the speech delivered by Pope UrbanⅡon 27 November 1095 at the Council of Clermont in France, which was largely due to the application of the agenda-setting theory in the speech. This paper will re-examine the speech of UrbanⅡfrom the perspective of agenda setting, and discuss the origin of the crusade by integrating other factors.